A randomized trial of treatment for anterior cruciate ligament reconstruction by radial extracorporeal shock wave therapy - Yufeng Song; Xinle Che; Zheyun Wang; Mengshi Li; Runjie Zhang; Dongming Wang; Qiongfang Shi (BMC Musculoskeletal Disorders, 2024)
Abstract Objective The aim of this study was to explore the effects of radial extracorporeal shock wave therapy (rESWT) in patients with anterior cruciate ligament(ACL) reconstruction(ACLR). Methods We conducted a randomized, controlled trial involving 72 eligible patients with ACL reconstruction in which we compared two strategies: the experimental group was standard rehabilitation plus rESWT and the control group was standard rehabilitation plus sham rESWT. The outcome was the change from baseline to 24 weeks in the average score on Lysholm knee joint score (LKS), range of motion (ROM), visual analogue scale (VAS) and International Knee Literature Committee (IKDC). Results Of 36 subjects assigned to rehabilitation plus rESWT, 4 lost to follow up. Of 36 assigned to rehabilitation plus sham rESWT, 5 lost to follow up. The LKS, ROM and IKDC scores of the experimental group were markedly increased at 3 and 6 weeks after treatment (P < 0.001), and the VAS was notably decreased (P < 0.001). However, there were no significant differences in the LKS, ROM, IKDC and VAS between the groups at 24 weeks after treatment (P > 0.05). Conclusion The strategy of rehabilitation plus rESWT had better functional outcomes after ACL reconstruction. As such, our study demonstrates that rESWT is essential for patients with ACL reconstruction. Early use of rESWT can improve joint function, pain relief and ability of daily living. rESWT has a positive effect on the overall rehabilitation of patients.